EVALUASI KUALITAS CATU DAYA LISTRIK DI BANDAR UDARA - JB. PURWADI (Langit Biru: Jurnal Ilmiah Aviasi, 2012)
To support the safe operation of the airport accomplay with fast, smooth, orderly, convenient and efficient, must be supported by aviation equipment that are reliable and qualified. For this purpose, the operation of aviation equipment needs a reliable power supply and stable or in other words, the electric power supply quality power supply that is reliable and comprehensive. The research method used in this evaluation includes a review of 5 (five) aspects, they are geographical aspects, technological aspects, economic aspects, technical aspect and operational aspects. Airport electrical power for the equipment at airports affected by the generation system, distribution networks and electrical load The results of the evaluation of the quality of the power supply at the airport are as follows a. The number of backup diesel generator at least 2 (two) unit with a capacity corresponding to the class airport. b. Electricity distribution network system with grounded categories customizable with electrical load being served c. Aviation safety equipment including non-linear load category, which requires quality power supply as well as contributors to the decline of good quality power supply. d. Electrical power quality improvements are generally not implemented in all airports in Indonesia, except the Soekarno Hatta airport and Ngurah Rai airport.